Factors associated with a low level of physical activity in adolescents from La Rioja (Spain) - Raúl Jiménez Boraita; Esther Gargallo Ibort; Josep María Dalmau Torres; Daniel Arriscado Alsina (Elsevier, 2022)
Introduction: Compliance with the recommendations regarding physical activity by adolescents is poor despite its proven benefits on their health. Objective: The objective of this study was to analyse the physical activity engagement in an adolescent population, evaluating its relationship with various indicators of physical and psychological health, as well as the influence of different sociodemographic variables as potential predictors. Methods: A cross-sectional study was applied to a sample of 761 students (14.51 ± 1.63 years) from 25 schools in La Rioja (Spain). Physical activity engagement, hours of nightly sleep, maximum oxygen uptake, health-related quality of life, self-esteem, body image satisfaction, adherence to the Mediterranean diet, body mass index, academic performance and various sociodemographic factors were analysed for all participants. Results: Being older, being a girl, having a low/medium socioeconomic level, living in unfavourable environments for practicing physical activity, not doing extracurricular sports activities, and being dissatisfied with body image were all predictors of a low physical activity engagement. Likewise, physical activity engagement reported positive associations with health-related quality of life, self-esteem, hours of nightly sleep, adherence to the Mediterranean diet and maximum oxygen uptake. Conclusions: Interventions aimed at promoting physical activity must take into account these predictive factors, trying to favor their performance, especially in the most vulnerable groups. Resumen: Introducción: El cumplimiento de las recomendaciones en torno a la actividad física por parte de los adolescentes es deficiente, a pesar de los demostrados beneficios sobre su salud. Objetivo: El objetivo del estudio fue analizar el nivel de actividad física en una población adolescente, evaluando su relación con diversos indicadores de salud física y psicológica, así como la influencia de diferentes variables sociodemográficas como potenciales factores predictores. Métodos: El estudio se llevó a cabo sobre una muestra de 761 estudiantes (14,51 ± 1,63 años) de 25 centros educativos de La Rioja (España). Se valoró el nivel de actividad física, horas de sueño nocturno, consumo máximo de oxígeno, calidad de vida relacionada con la salud, autoestima, satisfacción con la imagen corporal, adherencia a la dieta mediterránea, índice de masa corporal, rendimiento académico y factores sociodemográficos de los participantes. Resultados: Tener mayor edad, ser chica, tener un nivel socioeconómico bajo/medio, residir en entornos desfavorables para la práctica de AF, no realizar actividades deportivas extraescolares y estar disconforme con la imagen corporal resultaron ser factores predictores de un nivel de actividad física bajo. Asimismo, la actividad física reportó asociaciones positivas con la calidad de vida relacionada con la salud, autoestima, horas de sueño nocturno, adherencia a la dieta mediterránea y el consumo máximo de oxígeno. Conclusiones: Las intervenciones dirigidas a la promoción de la actividad física deben tener en cuenta estos factores predictores, tratando de favorecer su consecución especialmente en los grupos más vulnerables.